Dispensing process of four-side liquid crystal display module
By using multi-layer black UV glue filling and covering technology in the LCD display module, the loss of viewing angle and clarity caused by the inversion of TFT glass and CF glass and the Mura phenomenon are solved, and a higher viewing angle and clearer Display effect.
Patent Information
- Application Number
- CN202411277800.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
When the existing four-sided LCD display module is inverted with the CF glass, it leads to loss of viewing angle and picture clarity, and Mura phenomenon is prone to occur.
Using a dispensing process, a multi-layer colloid is formed by using black UV glue between TFT glass and CF glass, including colloids A, B and C layers, to fill the breaking surface and form a C-shaped enclosure, fill and cover The inner space of the dam ensures that the surfaces of each layer are flush and chromatic, thereby improving the four-sided effect and display quality of the module.
It realizes a true four-sided product, expands the viewing angle, improves the picture clarity, and effectively reduces the Mura phenomenon, significantly improving the display quality.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid crystal display, and in particular relates to a glue dispensing process for a four-sided liquid crystal display module. Background Art
[0002] The existing fake four-sided LCD module is to invert the TFT glass and CF glass to achieve the effect of a four-sided product. However, inverting the TFT glass and CF glass will lose some of the viewing angle and picture clarity. Moreover, when the TFT glass and CF glass are inverted, the FPC turning angle is large, which is easy to cause partial Mura phenomenon on the ground side. Summary of the invention
[0003] In order to solve the technical problems existing in the prior art, the purpose of the present invention is to provide a glue dispensing process for a four-sided liquid crystal display module.
[0004] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:
[0005] A glue dispensing process for a four-sided liquid crystal display module, wherein the four-sided liquid crystal display module comprises an upper polarizer, a CF glass and a TFT glass arranged in sequence from top to bottom, and the glue dispensing process comprises the following steps:
[0006] Step 1: Use black UV glue A to coat the TFT glass and the side of the CF glass to form a glue A layer to fill the gap between the CF glass and the TFT glass. After curing, the glue A layer is flush with the surface of the CF glass.
[0007] Step 2: Use black UV glue A to apply a layer of colloid B on the outside of the colloid A layer and the edges of both ends of the CF glass. After curing, a C-shaped dam is formed on the edge of the upper polarizer.
[0008] Step 3: Use black UV glue B to fill the internal space of the dam and cover the surface of the dam. After curing, a colloid C layer is formed. The colloid C layer is flush with the surface of the upper polarizer and connected to the side of the upper polarizer to form a whole without color difference.
[0009] Step 4: Use black UV glue C to coat the colloid layer D on the plane formed by the colloid layer A and the CF glass to fill the fault surface between the upper polarizer and the CF glass. After the colloid is cured, the colloid layer D is flush with the surface of the upper polarizer, and the colloid layer D and the upper polarizer become one;
[0010] When operating steps 1 to 3, step 4 is omitted; or, when operating steps 1 and 4, steps 2 and 3 are omitted; or, when operating steps 1, 2, and 4, step 3 is omitted.
[0011] Furthermore, the black UV glue A has a viscosity of 15000-20000 cps, a dispensing speed of 20-58 mm / s, a curing depth greater than 0.5 mm, and can be completely cured under a 405 nm ultraviolet curing lamp.
[0012] Furthermore, the colloid A layer has a width of 1-3 mm and a thickness of 0.1-1 mm.
[0013] Furthermore, the colloid A layer has a width of 2.2 mm and a thickness of 0.5 mm.
[0014] Furthermore, the viscosities of the black UV glue B and the black UV glue C are 15000-20000 cps and 100-500 cps, respectively, and the dispensing speeds are 20-50 mm / s, respectively.
[0015] Furthermore, the colloid B layer has a width of 0.1-1 mm and a thickness of 0.05-0.5 mm.
[0016] Furthermore, the colloid B layer has a width of 0.4 mm and a thickness of 0.1 mm.
[0017] Furthermore, the colloid D layer has a width of 3-4 mm and a thickness of 0.01-0.4 mm.
[0018] Furthermore, the colloid D layer has a width of 3.3 mm and a thickness of 0.15 mm.
[0019] Further, in step 1, a screw valve is used to apply black UV glue A on the TFT glass and the side of the CF glass;
[0020] In step 2, a screw valve is used to apply black UV glue A on the outside of the colloid A layer and the edges of both ends of the CF glass;
[0021] In step 3, use a spray valve to fill the inner space of the dam with black UV glue B and cover the surface of the dam;
[0022] In step 4, a precision scraper valve or a jet valve is used to coat the black UV glue C on the plane formed by the colloid A layer and the CF glass.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) Realize a true four-sided product;
[0025] (2) Provide a wider viewing angle;
[0026] (3) Effectively improve picture clarity;
[0027] (4) Effectively improve the Mura phenomenon and significantly enhance the image display quality. DETAILED DESCRIPTION
[0028] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0029] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.
[0030] The present invention discloses a glue dispensing process for a four-sided liquid crystal display module. The four-sided liquid crystal display module comprises an upper polarizer, a CF glass and a TFT glass which are sequentially arranged from top to bottom. The glue dispensing process comprises the following steps:
[0031] Step 1: Use black UV glue A to coat the TFT glass and the side of the CF glass to form a glue A layer to fill the gap between the CF glass and the TFT glass. After curing, the glue A layer is flush with the surface of the CF glass.
[0032] Step 2: Use black UV glue A to apply a layer of colloid B on the outside of the colloid A layer and the edges of both ends of the CF glass. After curing, a C-shaped dam is formed on the edge of the upper polarizer.
[0033] Step 3: Use black UV glue B to fill the internal space of the dam and cover the surface of the dam. After curing, a colloid C layer is formed. The colloid C layer is flush with the surface of the upper polarizer and connected to the side of the upper polarizer to form a whole without color difference.
[0034] Step 4: Use black UV glue C to coat the colloid layer D on the plane formed by the colloid layer A and the CF glass to fill the fault surface between the upper polarizer and the CF glass. After the colloid is cured, the colloid layer D is flush with the surface of the upper polarizer, and the colloid layer D and the upper polarizer become one;
[0035] When operating steps 1 to 3, step 4 is omitted; or, when operating steps 1 and 4, steps 2 and 3 are omitted; or, when operating steps 1, 2, and 4, step 3 is omitted.
[0036] In some embodiments, the black UV glue A has a viscosity of 15000-20000 cps, a dispensing speed of 20-58 mm / s, a curing depth greater than 0.5 mm, and can be completely cured under a 405 nm ultraviolet curing lamp.
[0037] In some embodiments, the colloid A layer has a width of 1-3 mm and a thickness of 0.1-1 mm.
[0038] In some embodiments, the viscosities of the black UV glue B and the black UV glue C are 15000-20000 cps and 100-500 cps, respectively, and the dispensing speeds are 20-50 mm / s, respectively.
[0039] In some embodiments, the colloid B layer has a width of 0.1-1 mm and a thickness of 0.05-0.5 mm.
[0040] In some embodiments, the colloid D layer has a width of 3-4 mm and a thickness of 0.01-0.4 mm.
[0041] In some embodiments, in step 1, a screw valve is used to coat black UV glue A on the TFT glass and the side of the CF glass.
[0042] In some embodiments, in step 2, a screw valve is used to coat the black UV glue A on the outside of the colloid A layer and the edges of both ends of the CF glass.
[0043] In some embodiments, in step three, a spray valve is used to fill the inner space of the dam with black UV glue B and cover the surface of the dam.
[0044] In some embodiments, in step 4, a precision scraper valve or a jet valve is used to coat the black UV glue C on the plane formed by the colloid A layer and the CF glass.
[0045] Example 1
[0046] A dispensing process for a four-sided liquid crystal display module, wherein the four-sided liquid crystal display module is specifically a liquid crystal display panel, mainly comprising an upper polarizer, CF glass and TFT glass arranged in sequence from top to bottom, and the dispensing process comprises the following steps:
[0047] Step 1: Use a screw valve and black UV glue A to apply a 2.2mm wide and 0.5mm thick layer of glue A on the TFT glass / CF glass side to fill the gap between the CF glass and the TFT glass. The cured glue A layer must be flush with the CF glass surface. The flatness of the glue A layer directly affects the appearance of the four-sided product.
[0048] The black UV glue A used in this step has the characteristics of high viscosity, high thixotropy, low curing shrinkage, and a curing depth greater than 0.5mm. The viscosity of black UV glue A is 15000cps, and the dispensing speed is 20mm / s. The high viscosity, high thixotropy and low curing shrinkage can meet the requirements of applying a nearly rectangular glue when using a screw valve for dispensing. The curing depth greater than 0.5mm allows the colloid to be completely cured under a 405nm UV curing lamp, ensuring that the colloid has sufficient adhesion on the TFT glass.
[0049] Step 2: Use a screw valve and black UV glue A to apply a 0.4mm wide and 0.1mm thick colloid B layer on the outside of the colloid A layer and the edges of both ends of the CF glass. After UV curing, a C-shaped dam is formed on the edge of the upper polarizer. The glue thickness must be strictly controlled in this step to avoid affecting the subsequent process steps and causing color differences at the edges of the colloid appearance.
[0050] Step 3: In the C-shaped dam coated in step 2, use the spray valve and black UV glue B to fill the internal space of the dam and cover the surface of the dam. The glue amount must be precisely controlled to prevent overflow. After curing, a glue C layer is formed.
[0051] The black UV glue B used in this step has the characteristics of low viscosity, high leveling, low curing shrinkage, and matte surface after curing. The viscosity of black UV glue B is 15000cps, and the dispensing speed is 20mm / s. The above characteristics can make the glue surface of the colloid C layer flush with the surface of the upper polarizer, connected to the side of the upper polarizer and become one, without color difference, so that the LCD display module forms the appearance of a true four-sided product.
[0052] Example 2
[0053] A dispensing process for a four-sided liquid crystal display module, wherein the four-sided liquid crystal display module is specifically a liquid crystal display panel, mainly comprising an upper polarizer, CF glass and TFT glass arranged in sequence from top to bottom, and the dispensing process comprises the following steps:
[0054] Step 1: Use a screw valve and black UV glue A to apply a 2.2mm wide and 0.5mm thick layer of glue A on the TFT glass / CF glass side to fill the gap between the CF glass and the TFT glass. The cured glue A layer must be flush with the CF glass surface. The flatness of the glue A layer directly affects the appearance of the four-sided product.
[0055] The black UV glue A used in this step has the characteristics of high viscosity, high thixotropy, low curing shrinkage, and a curing depth greater than 0.5mm. High viscosity, high thixotropy, and low curing shrinkage can satisfy the requirement of applying a nearly rectangular glue when dispensing using a screw valve. A curing depth greater than 0.5mm allows the colloid to be completely cured under a 405nm UV curing lamp, ensuring that the colloid has sufficient adhesion on the TFT glass.
[0056] Step 2: Use a precision scraper valve and black UV glue C to apply a 3.3mm wide and 0.15mm thick colloid D layer on the plane formed by the colloid A layer and the CF glass to fill the gap between the upper polarizer and the CF glass. After the colloid is cured, the glue surface must be flush with the surface of the upper polarizer. The colloid D layer and the upper polarizer become one, so that the LCD panel has the appearance of a true four-sided product;
[0057] The black UV glue C used in this step has the characteristics of high viscosity, high thixotropy, low curing shrinkage, and a matte surface after curing. The viscosity of black UV glue C is 500cps, and the dispensing speed is 20mm / s. The above characteristics can make the surface of the colloid D layer form a matte property similar to the haze of the upper polarizer after curing, and become one with the upper polarizer after the surface is leveled.
[0058] The rest is the same as in Example 1.
[0059] Example 3
[0060] A dispensing process for a four-sided liquid crystal display module, wherein the four-sided liquid crystal display module is specifically a liquid crystal display panel, mainly comprising an upper polarizer, CF glass and TFT glass arranged in sequence from top to bottom, and the dispensing process comprises the following steps:
[0061] Step 1: Use a screw valve and black UV glue A to apply a 2.2mm wide and 0.5mm thick layer of glue A on the TFT glass / CF glass side to fill the gap between the CF glass and the TFT glass. The cured glue A layer must be flush with the CF glass surface. The flatness of the glue A layer directly affects the appearance of the four-sided product.
[0062] The black UV glue A used in this step has the characteristics of high viscosity, high thixotropy, low curing shrinkage, and a curing depth greater than 0.5mm. High viscosity, high thixotropy, and low curing shrinkage can satisfy the requirement of applying a nearly rectangular glue when dispensing using a screw valve. A curing depth greater than 0.5mm allows the colloid to be completely cured under a 405nm UV curing lamp, ensuring that the colloid has sufficient adhesion on the TFT glass.
[0063] Step 2: On the plane formed by the colloid layer A and the CF glass, use the jet valve and black UV glue C to apply a colloid layer D with a width of 3.3mm and a thickness of about 0.15mm to fill the gap between the upper polarizer and the CF glass. After the colloid is cured, the glue surface must be flush with the surface of the upper polarizer. The colloid layer D and the upper polarizer become one, so that the LCD panel has the appearance of a true four-sided product;
[0064] The black UV glue C used in this step has the characteristics of high viscosity, high thixotropy, low curing shrinkage, and a matte surface after curing. The above characteristics can make the surface of the colloid D layer form a matte property similar to the haze of the upper polarizer after curing, and become one with the upper polarizer after the surface is leveled.
[0065] The rest is the same as in Example 1.
[0066] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.
[0067] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A dispensing process for a four-sided liquid crystal display module, wherein the four-sided liquid crystal display module comprises an upper polarizer, a CF glass and a TFT glass arranged in sequence from top to bottom, characterized in that: The dispensing process comprises the following steps: Step 1: Use black UV glue A to coat the TFT glass and the side of the CF glass to form a glue A layer to fill the gap between the CF glass and the TFT glass. After curing, the glue A layer is flush with the surface of the CF glass. Step 2: Use black UV glue A to apply a layer of colloid B on the outside of the colloid A layer and the edges of both ends of the CF glass. After curing, a C-shaped dam is formed on the edge of the upper polarizer. Step 3: Use black UV glue B to fill the internal space of the dam and cover the surface of the dam. After curing, a colloid C layer is formed. The colloid C layer is flush with the surface of the upper polarizer and connected to the side of the upper polarizer to form a whole without color difference. Step 4: Use black UV glue C to coat the colloid layer D on the plane formed by the colloid layer A and the CF glass to fill the fault surface between the upper polarizer and the CF glass. After the colloid is cured, the colloid layer D is flush with the surface of the upper polarizer, and the colloid layer D and the upper polarizer become one; When operating steps 1 to 3, step 4 is omitted; or, when operating steps 1 and 4, steps 2 and 3 are omitted; or, when operating steps 1, 2, and 4, step 3 is omitted.
2. The glue dispensing process of a four-sided liquid crystal display module according to claim 1, characterized in that: The black UV glue A has a viscosity of 15000-20000 cps, a dispensing speed of 20-58 mm / s, a curing depth greater than 0.5 mm, and can be completely cured under a 405 nm ultraviolet curing lamp.
3. The glue dispensing process of a four-sided liquid crystal display module according to claim 1, characterized in that: The colloid A layer has a width of 1-3 mm and a thickness of 0.1-1 mm.
4. The glue dispensing process of a four-sided liquid crystal display module according to claim 3, characterized in that: The colloid A layer has a width of 2.2 mm and a thickness of 0.5 mm.
5. The dispensing process for a four-sided liquid crystal display module according to claim 1, characterized in that: The viscosities of the black UV glue B and the black UV glue C are 15000-20000 cps and 100-500 cps respectively, and the dispensing speeds are 20-50 mm / s respectively.
6. The glue dispensing process for a four-sided liquid crystal display module according to claim 1, characterized in that: The colloid B layer has a width of 0.1-1 mm and a thickness of 0.05-0.5 mm.
7. The glue dispensing process of a four-sided liquid crystal display module according to claim 6, characterized in that: The colloid B layer has a width of 0.4 mm and a thickness of 0.1 mm.
8. The glue dispensing process for a four-sided liquid crystal display module according to claim 1, characterized in that: The colloid D layer has a width of 3-4 mm and a thickness of 0.01-0.4 mm.
9. The glue dispensing process for a four-sided liquid crystal display module according to claim 8, characterized in that: The colloid D layer has a width of 3.3 mm and a thickness of 0.15 mm.
10. The glue dispensing process of a four-sided liquid crystal display module according to claim 1, characterized in that: In step 1, a screw valve is used to apply black UV glue A on the TFT glass and the side of the CF glass; In step 2, a screw valve is used to apply black UV glue A on the outside of the colloid A layer and the edges of both ends of the CF glass; In step 3, use a spray valve to fill the inner space of the dam with black UV glue B and cover the surface of the dam; In step 4, a precision scraper valve or a jet valve is used to coat the black UV glue C on the plane formed by the colloid A layer and the CF glass.
